Checklist of Epicauta Dejean from America (Meloidae, Meloinae, Epicautini) - Campos Soldini, Maria Paula (2018)
This paper presents a comprehensive list of American Epicauta. Two hundred and sixty-four named species were recorded in this checklist based primarily on literature and museum records. Seventy-two species were included in the subgenus Macrobasis and 192 species into the nominotypic subgenus. Nomenclatural modifications are provided for E. langei Borchmann and E. nigripes Borchmann, both junior synonyms of E. pilme (Molina); E. albicincta Borchmann, junior synonym of E. suturalis (Haag-Rutenberg); E. lugubris Denier, junior synonym of E. tristis (Mäklin); and E. wagneri Pict, junior synonym of E. vicina (Haag-Rutenberg). Three hundred and ninety-two new records for South America are provided.